Analisa Kinerja Electrostatic Precipitator (ESP) Berdasarkan Besarnya Tegangan DC Yang Digunakan Terhadap Perubahan Emisi Di Power Boiler Industri Pulp And Paper - Afrian, Noza; Firdaus, Firdaus; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Coal-fired power plant can be a source of air pollution if the combustion of coal is not handled properly. The ash from the combustion of coal in a boiler to produce fly ash and bottom ash. Based on this condition, required tools to reduce or control the fly ash. The most effective tool to be used is the electrostatic precipitator (ESP). This observation purposes to Analyze the performance of ESP by the magnitude of the DC voltage used and able to improve the performance of ESP based on the magnitude of the voltage used to changes in emissions. Based on the observations made that the greater the emissions into the ESP, the greater the voltage, which is the actual maximum voltage of 70 kV and a maximum emission incoming (135 mg/Nm3), as well as the efficiency of ESP is also influence by the voltage generated, the greater the voltage generated then the efficiency would be increase.Keywords: Electrostatic precipitator (ESP), voltage, emissionsÂ